The Principal's Strategy in Implementing Religious Moderation: An Analysis of Islamic Education Management at Sukapura State Vocational School - zainal abidin; Zunaida, Laily; Ahmad Qusairi (Universitas Islam Negeri Raden Intan Lampung, 2025)
The successful implementation of religious moderation in schools depends heavily on the strategic role of the principal. This study aims to analyze the principal's leadership strategies as an Islamic education manager in managing religious diversity and realizing moderation at SMK Negeri Sukapura, a unique case study involving Muslim and Hindu students. Using a qualitative approach with a case study design, data were collected through in-depth interviews with 10 key informants, focused observations, and document analysis, conducted from July to September 2025. The findings indicate that the school's success is driven by transformational leadership that integrates the value of moderation into all management functions. The principal implemented strategies including: 1) Inclusive planning through the integration of moderation into the Vision/Mission/Work Plan (RKS); 2) Equitable organization through the formation of interfaith work teams; and 3) Accommodative implementation through equitable holiday policies and collaborative extracurricular programs. These strategies create a balanced and harmonious school culture (tawazun), making it an effective model for managing diversity. This research has significant implications for the development of Inclusive Islamic Education Management, demonstrating that moderate Islamic principles can serve as a successful leadership framework in heterogeneous public schools. Recommendations for further researchers are to conduct comparative studies of this leadership model in various diversity contexts or to conduct action research to test the effectiveness of specific programs developed by school principals.